Sistem Informasi Kehadiran Siswa Berbasis Web pada SMA Yappenda Jakarta - Reza Pahlevi; Mira Ziveria (UNIVERSITAS KALBIS, 2022)
SMA Yappenda Jakarta is one of the schools experiencing various obstacles in improving the quality of education in terms of recording student attendance. This school still uses manual methods or still uses books (written). Input errors often occur in the process of recording student attendance and the process of recapping student attendance data. This study aims to build a student attendance recording system at Yappenda Jakarta High School based on web, including the process of recording student attendance, student attendance data recap, with a Prototype system development method that includes system analysis using cross-functional diagrams and cause-effect diagrams, system design using Unified Modeling Language (UML), system development and programming using the Hypertext Preprocessor (PHP) programming language and My Structure Query Language (MySQL) database and system testing using black-box testing. The result of this research is a system that can be used to record student attendance at SMA Yappenda Jakarta.